Raising Bilingual-Biliterate Children in Monolingual Cultures - Xiaolei Cao (Studies in Applied Linguistics & TESOL, 2007)
Stephen J. Caldas and his wife, Suzanne, wanted to rear their children, John, Stephanie, and Valerie, to be bilingual and biliterate in both English and French in order to move easily between two monolingual cultures— Louisiana, USA, their primary residence, and Québec, Canada, where the family usually spent summer vacations. This longitudinal study or “family project,” in the author’s words, lasted 19 years from the author’s children’s early childhood to their late adolescence and is documented in Raising Bilingual-Biliterate Children in Monolingual Cultures. By elaborately recounting the strategies that he and his wife used in their children’s linguistic development, the author hopes to enlighten parents who also intend to bring up their children bilingually. Additionally, many findings are certainly appealing to both educators and researchers, including those related to the issues of peer influence on linguistic development during adolescence, the construction of bilingual identities, and the changes in accents and perceptions of accents that occur.